2022
DOI: 10.3390/plants11243540
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Polyphenols in Croatian Traditional Apple Varieties

Abstract: Apples and apple-based products are particularly interesting due to being a good source of polyphenols in an everyday diet. Recently there has been increased interest in the preservation of traditional apple varieties due to studies that suggest that traditional apple varieties have a higher content of polyphenols and antioxidant activity compared to commercial varieties. This study shows that traditional apple varieties contain higher concentration of polyphenolic compounds than conventional ones, such as chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The old apple cultivars, such as 'Austrougarka', 'Bobovec', and 'Božićnica', exhibited higher antioxidant capacities in both DPPH and ABTS assays compared to most commercial apple cultivars such as 'Golden Delicious', 'Idared', and 'Jonagold' (Table 8). These findings are consistent with previous research indicating that old apple cultivars generally possess higher levels of antioxidants than commercial cultivars [28,37,38,42]. Comparing the DPPH and ABTS assays, the values obtained from the ABTS assay were generally higher than those from the DPPH assay, which is in line with other studies that have found the ABTS assay to be more sensitive and thus yielding higher antioxidant capacity values.…”
Section: Gallic Acid Trans-ferulic Acid Chlorogenic Acid Caffeic Acid...supporting
confidence: 92%
“…The old apple cultivars, such as 'Austrougarka', 'Bobovec', and 'Božićnica', exhibited higher antioxidant capacities in both DPPH and ABTS assays compared to most commercial apple cultivars such as 'Golden Delicious', 'Idared', and 'Jonagold' (Table 8). These findings are consistent with previous research indicating that old apple cultivars generally possess higher levels of antioxidants than commercial cultivars [28,37,38,42]. Comparing the DPPH and ABTS assays, the values obtained from the ABTS assay were generally higher than those from the DPPH assay, which is in line with other studies that have found the ABTS assay to be more sensitive and thus yielding higher antioxidant capacity values.…”
Section: Gallic Acid Trans-ferulic Acid Chlorogenic Acid Caffeic Acid...supporting
confidence: 92%
“…This study was performed on a TSQ Quantum UltraTM triple quadrupole mass spectrometer equipped with a heated electrospray ionization source (HESI-II) (Thermo Scientific, San Jose, CA, USA) and an Accela Open self-sampler with a 20 µL loop. Instrumental conditions previously optimized by Skoko et al were used [73]. For the chromatographic separation, the column employed was Kinetex C18 (2.6 µm, 100 × 2.1 mm), which was obtained from Phenomenex (Torrance, CA, USA) and set at 50 • C. Water (A) (ultrapure water Milli-Q) and methanol (B) (Scharlau, Barcelona, Spain) were used as the mobile phase, both with 0.1% formic acid (98-100%, Merck, Darmstadt, Germany).…”
Section: Characterization Of Polyphenols Using Liquid Chromatography ...mentioning
confidence: 99%
“…Traditional apple varieties are also richer in individual polyphenolic compounds such as quercetin-3-rutinoside, procyanidin B1, B2, epicatechin, chlorogenic acid, etc. [24,[27][28][29]. Although the traditional apple varieties had a higher polyphenol content, it should not be forgotten that the stability of polyphenols is the most important nutritional value of food.…”
Section: Introductionmentioning
confidence: 99%